Pengaruh Audit Internal, Intellectual Capital Dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Alvina Renitha Chandra; Cris Kuntadi; Rachmat Pramukty (Politeknik Kampar, 2023)
This study aims to determine the effect of internal audit, intellectual capital and good corporate governance on the company's financial performance. The population of this study is banking companies listed on the Indonesia Stock Exchange from 2013 to 2016. In this study, the sampling method was a purposive sampling method with 43 companies as the population and 19 companies selected as samples. The data used is an annual report downloaded from the Indonesia Stock Exchange (IDX) website. The results of this study show that internal audit and intellectual capital have a positive and significant effect on the bank's financial performance, meaning that the better the internal audit and intellectual capital, the better the bank's financial performance. Meanwhile, good corporate governance has a negative and insignificant effect on bank profitability; this is because companies carry out good corporate governance not out of necessity, but to comply with established rules.